Effectiveness of Rota Vaccine among Children in Babylon Province, Iraq - Mudher Hassen Noor (Journal of Global Pharma Technology, 2018)
Acute diarrhea is passing of watery stool > 10 ml / kg / 24 h. which stay less than two weeks. Diarrhea account for 9% of death in children and about 0.71 million deaths / year in the world .Gastroenteritis, also called as infectious diarrhea, It means infection of gastrointestinal tract by certain organism, it could be either viral, bacterial or parasitic. And the virus is considered the most common. Rota virus is common in children while Norvo virus more common in adult. Rota virus is RNA virus belongs to the Reoviridea family. Most of children up to the age of 5 years are infected with this virus at least one time .The immunity will develop after the infection or vaccination with Rota virus. The aim of the study is to evaluate the effectiveness of Rota vaccine in modification of severity and prevalence of rotavirus infection among children in Babylon province A total of (1041) stool samples were collected from child with age from six months to five years old suffering from acute diarrhea who are admitted to the emergency room or to the wards of Babylon teaching Hospital for maternity and children. And all these stool samples were submitted for detection of rotavirus by a strips containing specific rotavirus Ab. The prevalence of positive rotavirus infection was (231) from (1041) with (22.22%) of all children with acute gastroenteritis from the age (6 months-5 years). We conclude that, Rotavirus infection was decrease significantly in our province after routine introduction of rotavirus vaccination